How Looking for Celiac‐Safe Wheat Can Influence Its Technological Properties. Issue 5 (11th July 2017) - Boukid, Fatma; Mejri, Mondher; Pellegrini, Nicoletta; Sforza, Stefano; Prandi, Barbara
Abstract: Because of the continuous increase in the prevalence of gluten‐related disorders, selection of wheat with a low content of immunogenic gluten epitopes could be an innovative alternative for prevention. In this review, the focus is on literature data concerning the deallergenization tools of wheat, which are mainly related to breeding approaches (classic and advanced) and processing operations (germination and fermentation). Until now, no safe wheat genotype has been identified, whereas decreasing wheat allergenicity is possible. On the other hand, the decrease of gluten or some of its epitopes can strongly affect technological properties. Thus, obtaining celiac‐safe gluten without affecting the technological properties of wheat could be considered as a new challenge that scientists will be facing. Celiac‐safe wheat‐based product development could be a great revolution in the market of foods for special medical purposes. The present paper is aiming to: (a) review the strategies and the approaches used, or that can be used, for developing low allergenic wheat: their utilities and limits were also discussed and (b) screen the impact of gluten reduction or removal on the quality of wheat end‐use products.